Câteva aspecte privind participarea în organizaţii de protecţie a mediului în România şi Europa - Laura Nistor (Sociologie Românească, 2009)
Environmental sociology frequently accentuates the role of active citizenship and civic involvement in the prevention of ecological problems, respectively problem-solving. Two ways in which active environmental citizenship can manifest itself are represented by the passive or active (volunteering) participation in environmental organizations (NGOs). In fact, such behaviors illustrate specific manifestations of the formal (associative) social capital, and from a political point of view circumscribe one important arena of environmental governance. There exist important contributions related to the case of formal social capital, however those studies investigating the case of participation in environmental associations are less frequent, at least in terms of exploring the social, demographic, axiological, political, etc. profiles of the participants. The present research aims to realize an individual-level study in this regard: based on data provided by the European Values Survey 1999 (Europe) and European Values Survey/Public Opinion Barometer, autumn 2005 (Romania) the profile of participants and volunteers in environmental NGOs will be explored.